The Semantic Distance, Fuzzy Dependency and Fuzzy Formulas - Dukić, Nedžad (Sarajevo Journal of Mathematics, 2024)
In this paper we establish a connection between one fragment fuzzy logic and the theory of fuzzy functional dependencies on the basic of the semantic distance. We give a way to interpret fuzzy functional dependencies as formulas in fuzzy logic. For a set of fuzzy dependencies F and single fuzzy functional dependency f, we show that F implies f as fuzzy functional dependencies if and only if F implies f under the logic interpretation. 2000 Mathematics Subject Classification. 03B52